Alfonso Peña and the enchanted threads of memory - Martins, Floriano (2022)
The writing of an In Memoriam is an exercise against oblivion, a commitment, in this case, to make the memory of the creative work of Costa Rican Alfonso Peña (1950-2022), a graphic and poetic creator whose underground polyphony still emerges in the complicity Iberoamerican surrealist.